2022
DOI: 10.1111/jen.13055
|View full text |Cite
|
Sign up to set email alerts
|

Growth, consumption and digestive enzyme activities of Spodoptera littoralis (Boisd) on various mung bean cultivars reveal potential tolerance traits

Abstract: Spodoptera littoralis (Boisd) is a worldwide pest of economic importance for agricultural crops. We investigated nutritional efficiency and digestive enzyme activity of S. littoralis on various mung bean cultivars, including Parto, Simite1, Simite2, VC6173A, VC3960, VC6368 and VC6371. Furthermore, various biochemical traits of mung bean cultivars, including protein, starch, total phenolic and flavonoid content, were measured to investigate their relationships with nutritional physiology of S. littoralis. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The plant nutrients that are absorbed by insects can simultaneously carry plant secondary compounds with adverse effects to the health of the feeding insects, and can significantly affect their growth, development, and physiological enzyme activities ( Cao et al 2015 , Li et al 2018 ). Differences in nutrient content or ingestion of protease inhibitors can directly affect the level of digestive enzyme metabolism of insects ( Guerreiro et al 2021 , Zamani Fard et al 2022 ). Significant differences in the activities of amylase, protease, and lipase were observed in insects after feeding on different foods ( Wang et al 2018 , Kotkar et al 2009 ), which affected the ability of insects to digest and absorb exogenous energy substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant nutrients that are absorbed by insects can simultaneously carry plant secondary compounds with adverse effects to the health of the feeding insects, and can significantly affect their growth, development, and physiological enzyme activities ( Cao et al 2015 , Li et al 2018 ). Differences in nutrient content or ingestion of protease inhibitors can directly affect the level of digestive enzyme metabolism of insects ( Guerreiro et al 2021 , Zamani Fard et al 2022 ). Significant differences in the activities of amylase, protease, and lipase were observed in insects after feeding on different foods ( Wang et al 2018 , Kotkar et al 2009 ), which affected the ability of insects to digest and absorb exogenous energy substances.…”
Section: Discussionmentioning
confidence: 99%
“…Digestive enzymes are important physiological components that play pivotal roles in the maintenance of normal growth, development, and survival of insects as well as their physiological and biochemical metabolism ( Terra and Ferreira 1994 , Erthal et al 2007 , Zamani Fard et al 2022 ). Therefore, digestive enzyme activity is often used as a key indicator for determining the physiological adaptability of insects ( Yuan et al 2020 , Zhi et al 2021 , Hemmati et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…When carrying out the bibliographic search on the insecticidal effects of EOs, and their main components, against S. frugiperda , it was observed that, in addition to the great variability in the methods implemented and the results obtained, this species had fewer toxicity studies carried out than the other pest species of the same genus. In contrast, Spodoptera littoralis , a generalist pest of legume crops such as Vigna radiata [ 94 ], is the species most frequently used for the study of the toxicity of EOs and their main components, followed by S. litura , the tobacco cutworm that attacks cotton, beans, tobacco, vegetables, and rice [ 95 ], and S. exigua , the beet armyworm [ 96 ]. Based on these observations, an analysis of the studies on toxicity in this complex of species was carried out in order to make a comparison with results observed for S. frugiperda .…”
Section: Toxicity Of Essential Oils Against Spodoptera Frug...mentioning
confidence: 99%
“…The Egyptian cotton leafworm, Spodoptera littoralis (Boisd) (Lepidoptera: Noctuidae), is a highly polyphagous and destructive pest which attacks a wide range of economically important crops throughout the world [ 1 , 2 , 3 , 4 ]. Lepidopteran larvae are of global phytosanitary concern due to their ability to attack a variety of plant structures, negatively affecting crop quality and causing economic losses [ 5 ].…”
Section: Introductionmentioning
confidence: 99%